The Role of The Uzbek Language in The Process of Globalization In The World Arena - Nasiba Jumaevna YARASHOVA (Genius Journals, 2024)
Uzbek is one of the 100 languages in the world with the status of a state language. However, there are also languages in the world that do not have such a high status, but are spoken by hundreds of millions.
Keywords: Language; Linguistics; National-Cultural